Brand Awareness De.U Coffee Bandung - Josephin Fenatama Angel; Putra Surya; Shania Putri Destari; Faranita Mustikasari (CV. Media Digital Publikasi Indonesia, 2023)
De.U Coffee is one of the famous cafes in the Bandung area. De.U Coffee has an inviting event community local in Bandung. The community in Bandung consists of various among. Organized events De.U Coffee since August 2020. Since the beginning of the opening, De.U Coffee has conceptualized a cafe that will routinely hold an event in the city of Bandung. Moment of this, the event is still routine, going on the joint event community bicycle every day Sunday morning. Apart from regular events, De.U Coffee is also a priority service best for the customer. De.U Coffee takes excellent care quality of the food and drink menu. Management also pays attention to the method waiter on duty, De.U Coffee, serving the customer. Hope from De.U Coffee raises growth in visitors and impressions of good messages from every consumer. Satisfaction with customers is matter most important for management De.U Coffee. They think about making customers repeat orders and become influenced, which suits those who have never been to De.U Coffee. In realizing matter that, of course, there are obstacles. An obstacle that occurs is a need for more commitment from the community. A community canceled the event on the day going to maintenance. Besides that, owner De.U Coffee also feels it challenging to give satisfaction in a manner. Keep going continuously to customers Because swift times change. Adaptation is matter most important in maintaining this. The analysis will later use quantitative analysis. The method we use is linear analysis regression. The Analysis For measure magnitude relationship and influence variable independent